The veterinary medicine in upgrading of competitiveness of Hungarian pig-production sector - Bíró, Oszkár; Ózsvári, László; Lakner, Zoltán (Acta Agraria Kaposváriensis, 2006)
The Hungarian pig-breeding has achieved considerable results in 70’s and 80’s of the last century, but after the privatisation and the collapse of former integration structures a considerable differentiation begun between the pig-breeding plants. Based on a direct-question survey the article analyses some main features of the activities of veterinarians in large-scale Hungarian pig-breeding units in 2004. Under rather unfavourable economic conditions of pig-breeding farms in numerous cases the owners of these enterprises do not pay the sufficient attention to the prevention and the analysis of information, which could be obtained by systematic survey of veterinary status of farms. However, as it became obvious by analysing the structure of veterinary medication, the increasing attention to preventive veterinary medicine could contribute to the improvement of veterinary status.
Keywords: swine; benchmarking; preventive medicine; veterinary strategy